Prevalence and risk factors of hearing loss in children with solid tumors treated with platinum-based chemotherapy - Eka D Edward; Nelly Rosdiana; Farhat Farhat; Olga Rasiyanti Siregar; Bidasari Lubis (Paediatrica Indonesiana, 2015)
Background The platinum-based chemotherapy drugs, cisplatin and carboplatin, are widely used in the treatment of several types of solid tumors. However, the treatment has side effects including hearing loss.Objective To evaluate the prevalence of hearing loss related to platinum-based chemotherapy and to identify associated factors.Methods A cross-sectional study was performed in Adam Malik Hospital, Medan, North Sumatera, from April to July 2012. Twenty-two subjects who fulfilled the eligibility criteria underwent otoacoustic emission evaluations. Eleven children had received cisplatin and eleven had received carboplatin. The association between hearing loss and risk factors was assessed using Fisher’s exact and Chi-square tests.Results Seven subjects with hearing loss were identified. Five of these patients (5 out of 11) had received cisplatin and 2 patients (2 out of 11) had received carboplatin. There was no statistically significant difference between carboplatin- and cisplatin-associated hearing loss (P=0.361). Neither gender (P=0.452) nor age (P=0.212) was related to hearing loss. However, higher cumulative chemotherapy doses (cisplatin >600 mg/m² and carboplatin >1800 mg/m²) were associated with hearing loss (P=0.022 and P=0.004, respectively).Conclusion Patients who had higher cumulative doses of platinum-based chemotherapy are at risk for developing hearing loss.